The Saga of Þórður kakali : The Icelandic Text - White, D. M. (Book collections on Project MUSE., 2020)
Icelandic literature, Nordic civil wars, saga, the Age of Sturlungar, thirteenth-century Iceland, Þórður kakali Sighvatsson.